Mapping QTLs with additive and epistatic effects for awn length and their effects on kernel-related traits in common wheat - Sun, Nina; Liu, Wei; Shi, Deyang; Zhao, Chunhua; Ou, Jinlian; Song, Yuanze; Yang, Zilin; Sun, Han; Wu, Yongzhen; Qin, Ran; Yuan, Tangyu; Jiao, Yanlin; et al. (Frontiers in Plant Science, 2024)
Key message Seven putative additive QTL and 30 pairwise epistatic QTL for awn length were identified and their effects on kernel-related traits were characterized. Wheat awns are crucial determinants of wheat yield due to their capacity to photosynthesize and exchange gas. Understanding the genetic basis of awn length (AL) is essential for improving wheat yield in molecular breeding programs. In this study, quantitative trait loci (QTL) of AL was analyzed using recombinant inbred lines (RILs) mapping population referred to as YY-RILs, which was derived from a cross between Yannong 15 (YN15) and Yannong 1212 (YN1212). Seven putative additive QTL and 30 pairwise epistatic QTL for AL were identified. Among them, five novel additive QTL (except qAl-2A and qAl-5A.2) and 30 novel pairwise epistatic QTL were identified. qAl-5A.1 was repeatedly identified in all the five environment datasets, which was considered to be one novel stable QTL for AL with minor additive effects. eqAl-2B.2-2 significantly interacted with eight loci and could be of great importance in regulating awn development. The genes associated with the major stable QTL of qAl-5A.2 and the minor stable QTL of qAl-2A were B1 and WFZP-A, respectively. Awn lengths exhibited significant genetic correlations with kernel weight and kernels per spike, which could affect grain protein content to a lesser extent. This study enhances our understanding of the genetic basis of awn development and identifies novel genes as well as marker for future genetic improvement of wheat yield.